Determination of the effect of cooking processes in pigmented native potatoes (Solanum tuberosum spp. andigena) on their bioactive compounds - Barragan Condori, Melquiades (2017)
The colors of native pigmented potatoes were extracted, purified and the anthocyanin spectra identified by FTIR and UV Visible in this solution. In the extract, the effect caused by different cooking processes (boiled, fried and microwaved) of native pigmented potatoes was quantified for total anthocyanins (CAT) and total polyphenols (PFT) before and after each process. The content of (CAT) in the native red potato (PST) and purple potato (PWQ) was 59.21 and 19.35 (mg cyanidin 3 glucoside / 100 g) respectively and once processed the potato (PST) decreases its (CAT) to 4.63 (mg cyanidin 3-glucoside / 100g) in the process of cooking by microwave oven, like potato (PWQ) at 1.31 (mg cyanidin 3-glucoside / 100g) in frying. The composition of (PFT) in potato (PST) and (PWQ) of 179.51 and 87.92 (mg gallic acid / 100g) respectively and after processing, are 125.27 (mg gallic acid / 100g) in the microwave oven of the potato (PST) and 12.19 (mg gallic acid / 100g) in potato frying (PWQ). The most severe decrease in (CAT) and (PFT) content, presented the native potato wenq'os, the most severe decrease in (CAT) and (PFT) content, presented the native fried purple potato, which determines that this cooking process has a greater degradation effect on the antioxidant compounds in native pigmented potatoes.